Compensation as a strategic asset : the new paradigm - Aquila, August J.; Rice, Coral L. (Wiley, 2009)
Everyone wants to work at a successful firm where the rewards are both financial and professional. What makes the top firms successful is not merely superior execution, though that's a good place to start, what makes them stand out is excellence at hiring and keeping the best, and having a smart succession plan in place. Partner compensation can be an effective tool in achieving these goals. Authors Aquila and Rice show how to use recruiting, retention, goal-setting, evaluation, and pay for performance practices recommended by the top CPA firm management consultants. This is the one guide you need, tailored specifically for professional practices, to implement the leading methods to align compensation with performance and strategic initiatives. You get: Analysis of leading views on performance management, hiring, and retention Specific, step-by-step guidance on how to implement compensation systems that align to goal-setting and performance measurement Methods for growing the compensation pie to pay for excellent results Compensation as a Strategic Asset shows how to align mission, vision, values, strategy, leadership, goal-setting, performance management and compensation to achieve long-term success at your firm.